An investigation into the profile and temporal evolution of firearm-related fatalities at Tygerberg Forensic Pathology Service Laboratory - Uren, Grace Amy (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2023.